Clinical and serological predictors of post COVID-19 condition–findings from a Canadian prospective cohort study - Collins, Erin; Galipeau, Yannick; Arnold, Corey; Bhéreur, Anne; Booth, Ronald; Buchan, Arianne C.; Cooper, Curtis; Crawley, Angela M.; McCluskie, Pauline S.; McGuinty, Michaeline; Pelchat, Martin; Rocheleau, Lynda; et al. (Frontiers in Public Health, 2024)
Introduction More than 3 years into the pandemic, there is persisting uncertainty as to the etiology, biomarkers, and risk factors of Post COVID-19 Condition (PCC). Serological research data remain a largely untapped resource. Few studies have investigated the potential relationships between post-acute serology and PCC, while accounting for clinical covariates. Methods We compared clinical and serological predictors among COVID-19 survivors with (n = 102 cases) and without (n = 122 controls) persistent symptoms ≥12 weeks post-infection. We selected four primary serological predictors (anti-nucleocapsid (N), anti-Spike, and anti-receptor binding domain (RBD) IgG titres, and neutralization efficiency), and specified clinical covariates a priori. Results Similar proportions of PCC-cases (66.7%, n = 68) and infected-controls (71.3%, n = 87) tested positive for anti-N IgG. More cases tested positive for anti-Spike (94.1%, n = 96) and anti-RBD (95.1%, n = 97) IgG, as compared with controls (anti-Spike: 89.3%, n = 109; anti-RBD: 84.4%, n = 103). Similar trends were observed among unvaccinated participants. Effects of IgG titres on PCC status were non-significant in univariate and multivariate analyses. Adjusting for age and sex, PCC-cases were more likely to be efficient neutralizers (OR 2.2, 95% CI 1.11–4.49), and odds was further increased among cases to report deterioration in quality of life (OR 3.4, 95% CI 1.64–7.31). Clinical covariates found to be significantly related to PCC included obesity (OR 2.3, p = 0.02), number of months post COVID-19 (OR 1.1, p < 0.01), allergies (OR 1.8, p = 0.04), and need for medical support (OR 4.1, p < 0.01). Conclusion Despite past COVID-19 infection, approximately one third of PCC-cases and infected-controls were seronegative for anti-N IgG. Findings suggest higher neutralization efficiency among cases as compared with controls, and that this relationship is stronger among cases with more severe PCC. Cases also required more medical support for COVID-19 symptoms, and described complex, ongoing health sequelae. More data from larger cohorts are needed to substantiate results, permit subgroup analyses of IgG titres, and explore for differences between clusters of PCC symptoms. Future assessment of IgG subtypes may also elucidate new findings.